Design and development of interferometr for hard disk surface measurement - Jong, Alexon Sze Chien. (Universiti Malaysia Sarawak (UNIMAS), 2008)
This thesis describes the design and set-up of the Michelson interferometer for hard disk surface measurement. This includes the optical st-up, imaging system and software design. The phase shifting method used in this project is Fourier transform method.